Eksplorasi dan Bioasai Berbagai Isolat Bacillus thuringiensis Lokal terhadap Larva Beberapa Jenis Serangga - Suryanto, Dwi; Chairani, Chairani; Rusika, Deddy; Lubis, Nita A.; Yurnaliza, Yurnaliza (Universitas Atma Jaya Yogyakarta, 2007)
Nine isolates of Bacillus thuringiensis of North Sumatra have been isolated from soil and dead larvae of Plutella xylostella. Bioassay of these isolates to larva of Heliothis armigera, Plutella xylostella, Aedes aegypti, and Culex sp. showed that the isolates have different spectrum and ability in controlling insect larvae. Interestingly, TU1 has similar ability to that of Dipel (B. thuringiensis var kurstaki strain HD-7) in controlling Dipteran (A. aegypti and Culex sp.) and Lepidopteran (H. armigera and P. xylostella). The others were not effective to Dipteran, but have various abilities to kill Lepidopteran. This result indicated that local isolates of B. thuringiensis of North Sumatra were varied in ability to kill different larvae.